Pelatihan Penerapan Aplikasi POM-QM Untuk Optimalisasi Hasil Penjualan Petatas pada UKM Saleh - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Habel S.J. Rieuwpassa; Jalminj Tindage; Frety Matahelumual (Yayasan Literasi Sains Indonesia, 2023)
Covid-19, which has attacked since 2019 until now, has reduced productivity. This makes the community uneasy, especially for Small and Medium Enterprises (SMEs). Many SMEs have been forced to close their business activities due to the Covid-19 pandemic. Various things have been attempted by relevant stakeholders so that SMEs continue to operate and develop despite being hit by the Covid-19 pandemic. This condition forces SMEs to adapt. Mr. Saleh Safar is one of the UKM players who trades at Remu Market, Sorong City, Southwest Papua Province. His merchandise is in the form of food, namely patatas. UKM owned by Mr. Saleh Safar has been operating since 1998 until now. During the pandemic there was a decrease in purchasing power which caused Mr. Saleh Safar to not know exactly how much optimal profit he would get from selling patatas. Seeing a situation like this, steps are needed to optimize sales. For this reason, the Community Service Team (PkM) at Victory Sorong University offers a POM-QM Application Application Training program for Optimizing Petatas Sales Results with the following stages of identifying problems, selecting problem-solving models, collecting data, processing data, implementing models, and evaluating results. This can help SMEs to innovate and maintain business activities, especially SMEs owned by Mr. Saleh Safar.